PROSES PENYELESAIAN PERKARA HARTA BERSAMA DI PENGADILAN AGAMA - Mahardhita, Gempur (Sekolah Tinggi Ilmu Fikih Syeikh Nawawi Tanara Serang, 2021)
When a marriage is terminated, a new legal effect arises. One of the legal impacts that arise is that the distribution of joint assets is required. Joint assets in marriage are property acquired during the marriage, this is as regulated in Article 35 paragraph (1) of Law Number 1 of 1974 concerning Marriage which reads